Mathematical Reprsentation Of Students In Solving Mathematic Problems Reviewed From Extrovert-Introvert Personality - Awaludin, Aulia Ar Rakhman; Selvia, Noni; Andrari, Finata Rastic (International Journal of Elementary Education, 2021)
This study discusses the mathematical representation of students in terms of introvert and extrovert personality types. In order to see the characteristics of mathematical representation in solving mathematical problems if seen from the personality type of each student. This research method is descriptive qualitative. The number of schools and students sampled from this study was taken with gradual data collection techniques (multistage sampling). Problem solving analysis used based on Krulik and Rudnik steps. Extrovert student personality types and introverted students do have a different mindset so that even in a few steps using the same representation but the tendency or habit represents a problem solving using a different form of representation. Extrovert students' personality types represent them more symbolically and almost all answers from type extrovert student are close to true when compared to introverted students.